Locked Down but Not Out: On-line Strength and Conditioning Provides A Viable Stimulus for Girls’ Football Players - Andrew Jones; Jonathan Emerson; John Franklin; Mike Graham; Matthew Wright (International Journal of Strength and Conditioning, 2024)
Strength and conditioning is important for physical preparation in girls’ association football players however, during the COVID-19 pandemic on-line “virtual” coaching replaced gym sessions. Using an retrospective observational design we aimed to quantify the internal responses from on-line and gym-based training in 27 (age 14.5 ± 0.9 yrs; stature 162 ± 6.0 cm; mass 56.8 ± 6.6 kg) girls’ football players from 1 FA Regional Talent Club.  Players provided session ratings of perceived exertion (RPE) via the CR-100© scale for global (sRPE-G), leg (sRPE-L),  upper-body (sRPE-U), and breathless (sRPE-B), and data were analysed through mixed linear modeling. Mean sRPE for gym and on-line were approximately “hard” to “very hard” (62 and 55 Arbitrary Units [AU]) for sRPE-G, “hard” for sRPE-L (57 and 53 AU), “somewhat hard” to “hard” (54 and 42 AU) for sRPE-U and “somewhat hard” (36 and 29 AU) for sRPE-B. We observed gym based training to provide significantly higher global (6.9, 95% confidence intervals; 3.9 to 9.9 Arbitrary Units[AU]) and upper-body (7.6, 3.6 to 11.6 AU). However, differences were less than our pre-defined minimal practical difference (8 AU) and sRPE-L and sRPE-B were statistically equivalent.  On-line strength and conditioning may be a viable alternative to gym-based sessions in girls’ association football players.